2009
DOI: 10.1155/2009/247121
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hepatitis C Antibody Levels in Gingival Crevicular Fluid and Saliva of Hepatitis C Seropositive Hemodialysis Patients

Abstract: Search for hepatitis C virus (HCV) in body fluids other than blood is important when assessing possible nonparenteral routes of viral transmission. However, the role of oral fluids in HCV transmission remains controversial. Our aim was to compare the prevalence of HCV antibody (HCV Ab) levels in saliva, and gingival crevicular fluid (GCF) of HCV seropositive hemodialysis patients. Serum, saliva and GCF samples were collected from thirty-nine patients. Samples were analyzed for HCV Ab using the Ortho HCV 3.0 SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This must be taken into account as the detection of anti‐HCV antibodies, but not the HCV RNA, may indicate a previously resolved infection . Interestingly, the both previous studies in which all patients had anti‐HCV antibodies and HCV RNA in serum were exactly the ones reporting the lowest sensitivity of anti‐HCV antibodies in saliva and crevicular fluid, with indexes varying from 12.8% to 46.3% , in spite of different kits used.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This must be taken into account as the detection of anti‐HCV antibodies, but not the HCV RNA, may indicate a previously resolved infection . Interestingly, the both previous studies in which all patients had anti‐HCV antibodies and HCV RNA in serum were exactly the ones reporting the lowest sensitivity of anti‐HCV antibodies in saliva and crevicular fluid, with indexes varying from 12.8% to 46.3% , in spite of different kits used.…”
Section: Discussionmentioning
confidence: 92%
“…Considering that salivary IgG and IgM derive mainly from gingival crevicular fluid, it can be speculated that this fluid would provide better results for detection of anti‐HCV IgG antibodies than whole saliva . Contrarily, in a recently published study, similar detection rates of anti‐HCV IgG antibodies were found in gingival crevicular fluid and saliva from patients with confirmed hepatitis C .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…During inflammation, the quantity of secreted gingival fluid is increased. In addition, inflamed gums bleed easily, facilitating the transfer of the HCV virus into the oral fluids such as saliva and gingival fluid [53,54]. The infectious potential of these fluids is still debatable and requires further research.…”
Section: Chronic Hepatitis C Infection From An Oral Health Perspectivementioning
confidence: 99%